22nd International Conference on Advanced Information Networking and Applications (Aina 2008) 2008
DOI: 10.1109/aina.2008.120
|View full text |Cite
|
Sign up to set email alerts
|

Improved TCAM-Based Pre-Filtering for Network Intrusion Detection Systems

Abstract: Abstract-With the increasing growth of the Internet, the explosion of attacks and viruses significantly affects the network security. Network Intrusion Detection System (NIDS) is developed to identify these network attacks by a set of rules. However, searching for multiple patterns is a computationally expensive task in NIDS. Traditional software-based solutions can not meet the high bandwidth demanded in current high-speed networks. In the past, the pre-filtering designed for NIDS is an effective technique th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Previous studies (e.g., [4], [16]) have shown that constructing an appropriate filtration mechanism is a promising way to handle overhead packets. Motivated by this line of research, we developed a trust-based packet filter using Bayesian inference to help reduce a large number of network packets for a single NIDS [21], where the trust-based approach was proven to be better than a statistic-based method [20], [23].…”
Section: A Background Of Single Trust-based Packet Filtermentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (e.g., [4], [16]) have shown that constructing an appropriate filtration mechanism is a promising way to handle overhead packets. Motivated by this line of research, we developed a trust-based packet filter using Bayesian inference to help reduce a large number of network packets for a single NIDS [21], where the trust-based approach was proven to be better than a statistic-based method [20], [23].…”
Section: A Background Of Single Trust-based Packet Filtermentioning
confidence: 99%
“…Later, Chang et al [4] provided two techniques to improve the FNP-like TCAM searching engine (FTSE) in high-speed networks, which was a two-stage architecture in detecting whether an incoming string contains patterns. The first approach performs pattern matching with a w-byte suffix instead of a w-byte prefix; and the second approach leverages the matching results from all groups excluding the first group.…”
Section: B Related Workmentioning
confidence: 99%
“…With technology scaling over the last 20 years, TCAM capacity has increased from 64Kb [57] to 9Mb [26], while typical array width has grown from 72 bits to 576 bits. Numerous networking applications have emerged to leverage the benefits of TCAM, including packet classification [29], access control list filtering [39], and network intrusion detection [11]. Table 1 shows a comparison among CMOS-based TCAM, SRAM, and DRAM chips.…”
Section: Associative Computing and Ternary Content Addressable Memoriesmentioning
confidence: 99%